Some Possibilities to Study New Prophylactics against Nerve Agents - Bajgar, J; Kassa, J; Kucera, T; Musilek, K; Jun, D; Kuca, K (Mini-reviews in medicinal chemistry, 2019)
Nerve agents belong to the most dangerous chemical warfare agents and can be/were misused by terrorists. Effective prophylaxis and treatment is necessary to diminish their effect. General principles of prophylaxis are summarized (protection against acetylcholinesterase inhibition, detoxification, treatment "in advance" and use of different drugs). They are based on the knowledge of mechanism of action of nerve agents. Among different examinations, it is necessary to test prophylactic effectivity in vivo and compare the results with protection in vitro. Chemical and biological approaches to the development of new prophylactics would be applied simultaneously during this research. Though the number of possible prophylactics is relatively high, the only four drugs were introduced into military medical practice. At present, pyridostigmine seems to be common prophylactic antidote; prophylactics panpal (tablets with pyridostigmine, trihexyphenidyl and benactyzine), transant (transdermal patch containing HI-6) are other means introduced into different armies as prophylactics. Scavenger commercionally available is Protexia®. Future development will be focused on scavengers, and on other drugs either reversible cholinesterase inhibitors (e.g., huperzine A, gallantamine, physostigmine, acridine derivatives) or other compounds.
Keywords: cholinesterasy; Cholinesterase Reactivators; Models, Molecular; Nerve Agents; nervová bojová látka; Animals; Humans; Cholinesterases; lidé; zvířata; molekulární modely; reaktivátory cholinesterasy